Overview of Safety Considerations with Highwall Mining Operations - George Gardner (International Conference on Ground Control in Mining, 2002)
The rapid growth of highwall mining in the Appalachian coalfields has resulted in unique safety concerns. Due to the concentration of activity at the base of the highwall and the potentially destabilizing influence of the mining process, proper mine planning and continual monitoring of the ground conditions is essential to ensure a safe and productive operation. This will also help to minimize the need to recover equipment that has become entrapped underground, and the subsequent hazards associated with a recovery operation. Adequate geotechnical site investigation and rational design methods should enable mine planners to properly account for the site-specific conditions that influence web and abutment pillar, roof, floor, and highwall stability. This paper examines the growth of highwall mining, provides a general overview of the various safety concerns, and reviews the modes of highwall failure as they relate to a highwall mining operation. Gcotechnical considerations that should be taken into account before and throughout the mining operation are emphasized. The importance of closely examining and monitoring highwall conditions for subtle signs of highwall instability will be discussed.